(untitled) (Международный научный журнал «Инженер», 2026)
This article presents an analysis of a series of experiments conducted to study the accumulation of chloroform by algae. The accumulation capacity of the natural biocenosis for retaining mineral, organic, and biological pollutants was examined. The first series of experiments was preliminary and did not yield clear results regarding the accumulation of chloroform by phytoplankton. The second series showed that the most intensive accumulation occurs during the initial hours of contact between chloroform and algae. In contrast, the third series demonstrated that no decrease in chloroform concentration was observed during the first hours, and accumulation occurred between the fourth and seventh days. The studies also revealed that the most active accumulation of chloroform happens during the initial hours of the first day. The higher the initial concentration of chloroform in water, the more intensively it is absorbed by algae. The results of these experiments suggest that the biouptake process can be recommended as an important stage in the preliminary purification of water and for practical application at drinking water treatment stations.